MATHEMATICAL PROBLEMS IN THE CONTEXT OF THE CHALLENGE OF DEVELOPING CRITICAL THINKING PROCEDURES IN FUTURE MATHEMATICS TEACHERS - Chkana, Yaroslav; Martynenko, Olena (Physical and Mathematical Education, 2024)
Problem Statement: The priority task of NUS educators is to adapt and implement progressive teaching methods to ensure the research-oriented nature of the educational process. In this context, training future mathematics teachers involves developing their mathematical competence and enhancing their critical thinking, which is crucial in the face of globalization, digitalization, and information overload. Investigating the role of mathematical problems in forming critical thinking procedures in future mathematics teachers is an important research direction. Materials and Methods: To address the problem, theoretical methods such as system analysis of domestic and foreign research works, generalization, and systematization of practical experience were applied. Results: The authors specify the stages of solving mathematical problems based on the involvement of critical thinking, describing the corresponding critical thinking procedures at each stage. A classification of mathematical problems based on their structure and levels of critical thinking engagement is developed, identifying four types: reproductive, reactive, productive, and creative. Specific examples of problem formulations and critical thinking procedures for solving them are provided for each type. Conclusions: Using various types of mathematical problems corresponding to the levels of critical thinking ensures a comprehensive approach to teaching. It will help future mathematics teachers acquire mathematical knowledge and develop the critical thinking necessary for their professional activities. The proposed classification allows for selecting tasks according to each student’s level of preparation and needs, fostering individualized educational trajectories, increasing motivation for learning, and helping students recognize their achievements.